SISTEM SMART GATE DENGAN MENGGUNAKAN WASTAFEL DAN SENSOR SUHU TOUCHLESS SENSOR BERBASIS FUZYY LOGIC CONTROL - Jatmika, Sunu; Aprilianto, Tria; Burhanudin, Dimas (P3M Politeknik Negeri Banjarmasin, 2022)
Health protocol standards are the main standards during the Covid-19 period. Because there is still a lack of public awareness in carrying out the protocol, one of which is that many people do not wash their hands before doing activities or even check body temperature sensors. In offices, whether private or government, tourist attractions, education and other health protocols still use employees, especially to check body temperature and lack of discipline in terms of checking users, so that people stay tipped, it is necessary the development of standard automation technology that must be carried out when the public will enter the office area or students before entering the school area through the gate. In order for the gate to be open, it must go through two standard health protocols, namely hand washing and checking body temperature. If one is not done and the value is not in accordance with the Covid task force standards, the gate will still be closed, for the hand washing process and temperature sensors use This touchless sensor is to reduce the level of risk of direct contact so that it will reduce the level of spread of the covid-19 virus. The results of this study from 50 respondents who tested the smart gate the success rate reached 90% percent success with 2 input parameters, namely through hand washing and body temperature sensors where the data was processed using fuzzy logic control. The method used for testing is using the functional tools/sensors used. While 10% is not successful because of the external light intensity factor when reading the sensor.